(untitled) (International Journal of Engineering Sciences & Management Research, 2021)
As God has honored man, so have international conventions honored him, and the Universal Declaration of Human Rights. Man in 1948 made clear at the beginning of his two-thirds articles by referring to the importance of preservation on human dignity as stated in the first paragraph of the preamble and did not exaggerate the authors The declaration considered the preservation of human dignity a basis for the rule of truth, justice and peace Within the national community and within the framework of the international community, which has been proven by national events and the international community during the past half century if wasting the dignity of human beings and peoples Violation of basic rights is a cause for concern, unrest, terrorism and conflict Armed.